Zarząd majątkami Polskiej Akademii Umiejętności w dwudziestoleciu międzywojennym - Biliński, Piotr; Skrzyński, Tomasz (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
During Poland’s twenty years of independence after the Great War the basic of functioning of the Polish Academy of Arts and Sciences were acres given by Archduke Karol Stefan Habsburg, Paweł Tyszkowski and Władysław Józef Fedorowicz. They were almost 20,000 hectares big and they consisted of three parts: forests, constructional areas and granges. Thanks to the income gained the Academy experienced the economic boom and its administrator, Stanisław Kutrzeba, could proudly say in 1938 that in the years of such market conditions it allocated one million złoty for scientific aims.